Mn2+ binding affects the thermal properties of an Antarctic esterase - Marchetti, A; Orlando, M; Mangiagalli, M; Lotti, M (2023)
Since temperature is considered a driving force in evolutionary pathways, the production of cold-active enzymes is one of the most endorsed strategies by psychrophilic organisms to thrive in cold environments. Usually, cold-active enzymes show high activities at low temperatures coupled with high structural flexibility and thermolability. A poorly considered aspect in cold adaptation is the role of metal ions. Generally, interactions of protein with metal ions are weak in psychrophilic enzymes, to foster their structural flexibility, while are widespread in thermophilic enzymes, to enhance their structural rigidity. Here, we report the characterization of a GDSx esterase (M-Est) identified in the genome of Marinomonas sp. ef1, an Antarctic marine bacterium able to grow in the temperature range from 4 to 22°C. M-Est is active on short chain esters and can be considered a true cold-active enzyme, as it displays a Topt of 5°C and marked thermolability. Unlike several cold-active enzymes, we observed that the metal ion Mn2+ enhances catalytic efficiency and thermostability of M-Est, besides promoting conformational changes. The binding between Mn2+ ion and M-Est has been extensively investigated through a complementary set of biochemical, biophysical, and computational techniques. Our results suggest that manganese binding is an unconventional solution adopted by M-Est to mitigate the detrimental effect of mild temperature.